Motivating Truthful Subordinate Reporting: An Experimental Investigation in a Two‐Subordinate Context* - CHOW, CHEE W.; HIRST, MARK K.; SHIELDS, MICHAEL D. (Contemporary Accounting Research, 1994)
Abstract. This experimental study tests the predicted effects of three performance‐contingent pay schemes on subordinate misrepresentations: profit sharing, a single‐subordinate truth‐inducing scheme, and the Groves scheme. A contribution not found in prior experimental research is the introduction of the distinction between direct and indirect misrepresentations. The results show that, as predicted, the three schemes have different abilities to deter the two types of misrepresentations. The fewest direct and indirect misrepresentations occur under the Groves scheme and the most under the linear profit‐sharing scheme. There is no significant difference between the single‐subordinate truth‐inducing scheme and the Groves scheme in the incidence of direct misrepresentations, but indirect misrepresentations are significantly more frequent under the former. Résumé. La présente étude expérimentale vise à tester certaines hypothèses relatives aux résultats de l'application de trois structures salariales liées au rendement sur les déclarations trompeuses des subordonnés: la participation linéaire aux bénéfices, une structure salariale individuelle favorisant la franchise et la structure Groves. Cette étude se démarque des etudes expérimentales antérieures en ce qu'elle introduit une distinction entre l'information trompeuse directe et indirecte. Les résultats révèlent que, conformément aux hypothèses, les trois structures salariales présentent des capacités différentes de décourager les deux formes de déclarations trompeuses. La structure Groves est celle qui occasionne le plus petit nombre de déclarations trompeuses directes et indirectes, tandis que la participation linéaire aux bénéfices est celle qui en occasionne le plus. Il n'existe pas de différence significative entre la structure salariale individuelle favorisant la franchise et la structure Groves en ce qui a trait à l'occurrence des déclarations trompeuses directes, mais les déclarations trompeuses indirectes sont beaucoup plus fréquentes dans le cas de la structure salariale individuelle.